Oral history in the visual arts - Partington, Matthew; Sandino, Linda (Bloomsbury, 2013)
Through a wide range of international case studies, this interdisciplinary volume maps how oral history interviews contribute to a relational practice that is creative, rigorous and ethically grounded.